ANALISIS PENGARUH BOPO, NIM, GWM, LOR, PPAP DAN NPL TERHADAP ROE PADA BANK GO PUBLIC DAN NON GO PUBLIC DI INDONESIA PERIODE TAHUN 2007-2009 - Wati, Erna (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2011)
In order to define aÂ bank's performance, we may determine it from many aspects such as its profitability. Return on Equity is an indicator for the investors to measure how efficient the profit produced from the equity they've invested.Â Return on Equity is aÂ financial ratio of Net- Interest After Tax to Equity.This research analyzes the influences of Operational Cost to Income Ratio, Net Interest Margin, Reserve Requirement, Loan to Deposit Ratio, Producing Assets Reserves, Non-Performing Loan to Return on Equity of go-public banks compared with non go-public in Indonesia over the period from 2007 to 2009.